Self-Censorship and Cancel Culture: A spiral of silence in the digital age - Tislér, Ádám (POLARITIES, 2023)
Cancel culture is one of the most debated social phenomena in Western countries in recent years. With witch-hunts sweeping across the online space, seemingly no one can hide if they have ever done or said something that groups fighting for social justice consider unacceptable or politically incorrect. These groups do not tolerate any dissent, they take a dogmatic stance and there is little to no room for constructive debates. But what is the reason why these groups are so successful in asserting their positions in the Western part of the World, apparently without any opposition?